Customers’ Perceptions Toward Organised Retailing: An Analytical Study of Selected Cities in Odisha (Journal of Informatics Education and Research, 2026)
The expansion of organised retailing in India has reshaped consumer behaviour and market dynamics, particularly in developing regions such as Odisha. This study aims to assess the role of organised retailing in sustaining competitiveness within a hypercompetitive market environment and to identify differences in customer perceptions across various urban centres. The research is based on primary data collected through a structured questionnaire from customers visiting organised retail outlets in selected cities of Odisha. A quantitative research design was adopted, employing statistical techniques such as descriptive analysis, correlation, and ANOVA to test the formulated hypotheses. The first hypothesis (H1) examined the significance of organised retailing in maintaining market competitiveness, while the second hypothesis (H2) tested the variation in customers’ perceptions among cities. The findings indicate that organised retailing significantly contributes to sustaining competitiveness by offering improved product assortment, enhanced service quality, and better shopping experiences. The results reveal notable differences in customer perceptions across cities, influenced by demographic and socio-economic factors. The study highlights that customer loyalty and satisfaction depend on consistent service delivery and store innovation. The outcomes of this study provide valuable insights for retailers and policymakers to develop effective strategies for strengthening organised retail formats and promoting sustainable retail growth in Odisha’s evolving market context.